HOST-RESTRICTED RANGE OF H5N1 AVIAN INFLUENZA VIRUSES ASSOCIATED WITH CHARACTERS OF POLYMERASE COMPLEX OF PB2 AND PB1-F2 PROTEINS - NLP Indi Dharmayanti; Risza Hartawan (Indonesian Agency for Agricultural Research and Development, 2015)
Epidemiological studies on H5N1 avian influenza viruses indi-cated that the viruses do not transmit efficiently from human to human. Transmissibility of viruses among human population is very complex and polygenic. Studies on molecular determinants facilitating interspecies transmission of the viruses suggested that two polymerase complex proteins such as PB2 and PB1-F2 are important. PB2 is critical in determining the host specificity, whereas mutations in PB1-F2 increase the viral virulence. The study aimed to characterize the polymerase complex of PB2 and PB1-F2 proteins of H5N1 avian influenza viruses isolated from Indonesia. The DNA samples encoding the PB2 and PB1-F2 complex proteins of several H5N1 isolates were sequenced and analyzed. Pathogenicity of the viruses was studied in both avian and mammal models. The sequencing results showed that there was no mutation in both proteins of PB2 and PB1-F2 of the avian influenza virus isolates. The molecular character for host specificity was consistent with the animal experiment results. The H5N1 virus isolates were only infectious and pathogenic in chickens, but not in BALB/C mice as the mammal model. The study suggests that host range of H5N1 virus isolates of Indonesia is restricted to poultry and not transmisible to mammal model used in this study.